Topical infliximab for the suppression of wound healing following experimental glaucoma filtration surgery - Turgut, Burak; Eren, Kenan; Akin, Mehmet Mustafa; Demir, Tamer; Kobat, Sabiha (Dove Medical Press Ltd, 2014)
Background: The purpose of this work was to look into the effects of infliximab on wound healing in experimental glaucoma filtration surgery and to compare the antifibrotic effects of this agent to that of mitomycin-C (MMC). Methods: Twenty-eight male New Zealand White rabbits were randomly assigned to four groups, each including seven rabbits: control group, sham group, MMC group, and infliximab group. The rabbits in the control group were not operated on and did not receive any treatment. The rabbits in the sham group underwent trabeculectomy and had one drop of saline instilled four times a day for 14 days. The rabbits in the MMC treatment group underwent trabeculectomy, and a sponge soaked in 0.4 mg/mL MMC was applied intraoperatively to the scleral surgical site for three minutes. The rabbits in the infliximab treatment group underwent trabeculectomy and one drop of 10 mg/mL infliximab was instilled four times a day for 14 days after surgery. On day 14 of the experiment, the operated and control eyes were enucleated and histologically and immunohistochemically analyzed. Results: The mean fibroblast and mononuclear cell (MNC) numbers and the mean immunostaining intensities of transforming growth factor-beta (TGF-beta), fibroblast growth factor-beta (FGF-beta), and platelet-derived growth factor (PDGF) in the sham group were higher than those of the control group (P<0.01). The mean fibroblast and MNC numbers and the mean immunostaining intensities of TGF-beta, FGF-beta, and PDGF in the MMC and infliximab groups were statistically significantly lower than those of the sham group (P<0.01). The mean fibroblast and MNC numbers and the mean TGF-beta, FGF-beta, and PDGF immunostaining intensities of the MMC and infliximab groups were similar (P>0.05). Conclusion: Our study suggests that topical infliximab effectively suppresses the subconjunctival wound healing response after experimental glaucoma filtration surgery, reducing the MNC and fibroblast numbers and immunostaining intensities of TGF-beta, FGF-beta, and PDGF.
Keywords: mitomycin-C; trabeculectomy; anti-TNF; growth factors